Durability of alkali-activated binders: a clear advantage over Portland cement or an unproven issue? - Pacheco-Torgal, F. (2012)
The alkali activation of alumino-silicate materials is a complex chemical process evolving dissolution of raw materials, transportation or orientation and polycondensation of the reaction products. Publications on the field of alkali-activated binders, state that this new material is likely to have high potential to become an alternative to Portland cement. While some authors state that the durability of these materials constitutes the most important advantage over Portland cement others argue that it’s an unproven issue. This paper presents a review of the literature about the durability of alkali-activated binders. The subjects of this paper are resistance to acid attack, alkali–silica reaction, corrosion of steel reinforcement, resistance to high temperatures and to fire, resistance to freeze–thaw. Special attention is given to the case of efflorescences, an aspect that was received very little concern although it is a very important one.